PENGARUH BUDAYA KERJA DAN KEDISIPLINAN TERHADAP KINERJA MELALUI KOMITMEN PEGAWAI DINAS KEBUDAYAAN, KEPEMUDAAN DAN OLAHRAGA SERTA PARIWISATA KABUPATEN TUBAN - Wahyudhi, Priyo Agus; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of work culture, discipline, and organizational commitment on employee performance, as well as the mediating role of commitment at the Department of Culture, Youth and Sports, and Tourism of Tuban Regency. A quantitative approach was used with a census method, involving all 55 employees as respondents. Data analysis was conducted using Partial Least Squares (PLS) with the help of SmartPLS 3.0 software. The results indicate that work culture, discipline, and organizational commitment each have a positive and significant effect on employee performance. Furthermore, organizational commitment was found to mediate the relationship between work culture and performance, as well as between discipline and performance. These findings suggest that improving work culture and discipline will be more effective in enhancing employee performance when accompanied by strong organizational commitment. Therefore, management should strengthen work culture, discipline, and commitment to achieve optimal organizational performance.